Optimization of Calcium and Phosphorus levels in the Diet of Cirrhinus mrigala (Hamilton, 1822) Fingerlings - Bhatnagar, Anita; Rajaharia, Neelam; Dhillon, Oshin (Indian Journal of Animal Nutrition, 2019)
A dietary experiment was carried out to evaluate the optimum levels of calcium and phosphorus in the diet of mrigal, Cirrhinus mrigala. Ten dietary treatments were performed, fed on diet supplemented with additional Calcium (Ca) and Phosphorus (P) in ratios 0:0 (C), 5.0:2.5 (D1), 5.0:3.75 (D2), 5.0:5.0 (D3), 7.5:2.5 (D4), 7.5:3.75 (D5), 7.5:5.0 (D6), 10:2 (D7), 10:3.75 (D8), 10:5.0 (D9), respectively for 90 days in triplicates. Different concentrations of phosphorus as di-hydrogen-orthophosphate (0.25, 0.375 and 0.5 100g-1 of diet) and calcium as calcium chloride (0.5, 0.75 and 1.0 g 100 g-1 of diet) were added to the basal diet. The Ca and P content of the holding water were 62.64Â±2.60 mg L-1 and 0.04Â±0.001 mg L-1, respectively. Growth performance increased significantly (P<0.05) with 3.75 g kg-1 of phosphorus and 7.5 g kg-1 of calcium, but decreased beyond this concentration. Total ammonia excretion and reactive phosphate production was significantly high in the fish fed groups below and above this concentration. Fingerlings showed deficiency symptoms such as reduced growth, low intestinal enzymatic activity when fed on diets other than D5 clearly revealing that the concentration of 7.5 g kg-1 of calcium and 3.75 g kg-1 of phosphorus in the diet is optimum for enhancing growth in C. mrigala.